Strategi Pengelolaan Berkelanjutan Ikan Terubuk (Tenualosa macrura) di Provinsi Riau: Sintesis Bioekologi, Sosial-Ekonomi, dan Kelembagaan Berbasis Scoping Review - Romie Jhonnerie; Juliana; Eko Prianto; Miswadi; Dhita Widhiastika; Riska Fatmawati; Yossi Oktorini (Jurusan Ilmu Kelautan dan Perikanan Politeknik Negeri Pontianak, 2025)
The terubuk fish (Tenualosa macrura) is an endemic species that holds high economic value and significant socio-cultural importance for the people of Riau, Indonesia. However, excessive fishing pressure and estuarine habitat degradation have drastically reduced its population. This study aims to map and synthesize existing scientific knowledge related to the conservation and management of the terubuk fish through a scoping review approach. A total of 38 documents were examined, of which 34 met the inclusion criteria based on the PRISMA-ScR guidelines. The analyzed literature was categorized into six major thematic areas: bioecology, socio-economics, institutional aspects, legal frameworks, cultural values, and environmental factors. The synthesis reveals heavy pressure on fish stocks, high economic vulnerability among small-scale fishers, weak law enforcement, and a declining role of local wisdom in conservation practices. These findings emphasize the urgency of developing an integrated management strategy that combines ecological science, socio-economic conditions, and the cultural values of coastal communities. Such an approach could serve as the foundation for designing more adaptive and effective policies to ensure the long-term sustainability of the terubuk fish population in Riau waters.